Initiation of the transcriptional response to hyperosmotic shock correlates with the potential for volume recovery. (5th July 2013) - Geijer, Cecilia; Medrala‐Klein, Dagmara; Petelenz‐Kurdziel, Elzbieta; Ericsson, Abraham; Smedh, Maria; Andersson, Mikael; Goksör, Mattias; Nadal‐Ribelles, Mariona; Posas, Francesc; Krantz, Marcus; Nordlander, Bodil; Hohmann, Stefan
Abstract : The control of activity and localization of transcription factors is critical for appropriate transcriptional responses. In eukaryotes, signal transduction components such as mitogen‐activated protein kinase (MAPK) shuttle into the nucleus to activate transcription. It is not known in detail how different amounts of nuclear MAPK over time affect the transcriptional response. In the present study, we aimed to address this issue by studying the high osmolarity glycerol (HOG) system in Saccharomyces cerevisiae . We employed a conditional osmotic system, which changes the period of the MAPK Hog1 signal independent of the initial stress level. We determined the dynamics of the Hog1 nuclear localization and cell volume by single‐cell analysis in well‐controlled microfluidics systems and compared the responses with the global transcriptional output of cell populations. We discovered that the onset of the initial transcriptional response correlates with the potential of cells for rapid adaptation; cells that are capable of recovering quickly initiate the transcriptional responses immediately, whereas cells that require longer time to adapt also respond later. This is reflected by Hog1 nuclear localization, Hog1 promoter association and the transcriptional response, but not Hog1 phosphorylation, suggesting that a presently uncharacterized rapid adaptive mechanism precedes the Hog1 nuclear response. Furthermore, we found that the period of Hog1 nuclear residence affects the amplitude of the transcriptional response rather than the spectrum of responsive genes. Abstract : Signal transduction components such as MAP kinases shuttle into the nucleus to activate transcription. It is not known how different amounts of nuclear MAPK over time affect the transcriptional response. We found that the initial transcriptional response correlates with the potential of cells for rapid adaptation and that the period of Hog1 nuclear residence affects the amplitude of the transcriptional response rather than the spectrum of responsive genes.